The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1016/j.orthres.2005.04.003.1100230610
|View full text |Cite
|
Sign up to set email alerts
|

Cellular basis for age-related changes in fracture repair

Abstract: The goal of this work was to define cellular and molecular changes that occur during fracture healing as animals age. We compared the molecular, cellular, and histological progression of skeletal repair in juvenile (4 weeks old), middle-aged (6 months old), and elderly (18 months old) mice at 3, 5, 7, 10, 14,21,28, and 35 days post-fracture, using a non-stabilized tibia fracturqmodel. Our histological and molecular analyses demonstrated that there was a sharp decline in fracture healing potential between juven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(68 citation statements)
references
References 25 publications
0
66
1
1
Order By: Relevance
“…Serial 10‐µm longitudinal sections were collected throughout the entire callus tissue using a Leica microtome (Leica Microsystems GmbH, Wetzler, Germany). To compare fracture repair rates between mdx and wild‐type mice, histomorphometric analyses of total callus, cartilage, and trabecular bone volumes were performed via Adobe PhotoShop (Adobe, Inc., San Jose, CA, USA) as described in Colnot and colleagues and Lu and colleagues . A minimum of seven equidistant sections spaced at 300 µm apart throughout the callus was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Serial 10‐µm longitudinal sections were collected throughout the entire callus tissue using a Leica microtome (Leica Microsystems GmbH, Wetzler, Germany). To compare fracture repair rates between mdx and wild‐type mice, histomorphometric analyses of total callus, cartilage, and trabecular bone volumes were performed via Adobe PhotoShop (Adobe, Inc., San Jose, CA, USA) as described in Colnot and colleagues and Lu and colleagues . A minimum of seven equidistant sections spaced at 300 µm apart throughout the callus was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Physiological changes associated with ageing have a great effect on vascularization and angiogenesis during fracture healing . Lu et al observed juvenile (4 weeks), middle‐aged (6 months) and elderly (18 months) mice, with non‐stabilized tibia fractures, and compared cellular, molecular and histological progression of fracture repair. Results indicated decreased bone formation, impaired bone remodeling, delayed angiogenic invasion of cartilage, prolonged endochondral ossification and delays in cell differentiation associated with aging.…”
Section: Comorbidities Influencing Fracture Healingmentioning
confidence: 99%
“…Although the flanking ribs provide sufficient stability around the resection such that no external fixator is needed, the repair zone is under the constant movement and strain of lung inflation/deflation. It has been recognized that during bone repair, too much movement can be inhibitory to healing while some movement appears to be important for generating a cartilage intermediate 13,14 . At this point, it is not clear, however it is possible that formation of a cartilage intermediate may be a key step for effective large-scale repair.…”
Section: Discussionmentioning
confidence: 99%